A Patient of Cerebrospinal Fluid Leakage with Abducens Nerve Palsy Effectively Treated with Epidural Blood Patch - Ono, Takaaki; Goto, Katsutoshi; Miki, Atsushi; Ieki, Yoshiaki; Haruishi, Kazuko; Takai, Hiroki; Uno, Masaaki; Araki, Syunsuke; Kiryu, Junichi (Neuro-Ophthalmology Japan, 2023)
We present a patient with cerebrospinal fluid (CSF) leakage with abducens nerve palsy effec tively treated with epidural blood patch (EBP). A 40-year-old woman visited a nearby ophthalmol ogist for an orthostatic headache with nausea and was diagnosed with a migraine. After three weeks, she developed diplopia. Contrast-enhanced magnetic resonance imaging revealed diffuse enlargement of the subdural space and diffuse dural enhancement. She was referred to our hospital for further examination and treatment for suspected CSF leakage including intracranial hypotension syndrome. At the first visit, visual acuity was 1.0 in both eyes, and intraocular pressure was 13 and 15 mmHg in the right and left, respectively. There were no abnormal findings in the anterior segment, optic media, or fundus. Alternate prism cover test (APCT) result was 25 and 16 prism diopter (PD) esotropia at the far distance and near, respectively, and Hess red-green test showed limited abduction in the right eye. Computed tomography myelography revealed CSF leakage, and the patient was diagnosed with abducens nerve palsy due to CSF leakage and intracranial hypotension syndrome. Two weeks after the initial visit, the headache resolved but abducens nerve palsy remained, and EBP was performed one month after the initial visit. After one month of treatment, diplopia had disappeared, the APCT result was 4 PD esophoria at far and near distance, and limited abduction in the right eye had improved. CSF leakage should be considered in patients with abducens nerve palsy with orthostatic headache, and EBP may be useful in the treatment of CSF leakage.